RE-DESAIN LAYOUT GALANGAN UNTUK OPTIMALISASI PROSES PEMBANGUNAN DAN REPARASI KAPAL - Imelda Septi Andreani (2022)
The layout of an industry requires proper planning to optimize the production process of an item, one of the most is the shipbuilding industry in Indonesia with a highly complex work system and systematic work in it. For example, the building and repair dock shipyards have a land area of ±19,614 m² with various types of work processes and different facilities. The layout of the shipyard facilities used previously was less effective in the material handling process of ship production, this is because the distance between departmental stations is far enough to take a long time. For this reason, planning a re-design layout of the shipyard is necessary by comparing the material handling distance with the material handling cost of the current layout with an alternative layout using the CRAFT algorithm of WinQsb software and the proposed layout by considering the degree of proximity or Activity Relationship Chart (ARC) then assisted with WinQsb software to analyze distance drop and material handling cost. Based on the analysis of this study, it is known that the proposed layout re-design planning with ARC considerations can optimize material handling cost by 13.6% from the initial layout of Rp 13.626.629 to Rp 11.772.165 by reducing the material handling distance by 143 m. While planning alternative layout re-designs through software WinQsb was able to reduce cost by 7.82% from the initial material handling cost initial layout to Rp 12.560.420. The estimated material handling occurs in 11.46 minutes without any obstacles during the process.